EPIDEMIOLOGY OF OSTEOPOROTIC FRACTURES OF VERTEBRAS IN ELDERLY AND SENILE PERSONS - V. G. Pustozerov (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The information about epidemiology of osteoporotic injuries of vertebras among people of elderly and senile age of Irkutsk is provided in the article. It is shown that frequency of these injuries is 28 % (33,9 % in women and. 22,2 % in men), and. osteoporotic fractures of vertebras were revealed, at 23,6 % (at 28,9 % of women and. at 18,3 % of men) semi-quantitative and. at 22,8 % (28,3 % and. 17,2 % respectively) quantitative by radiological methods of an assessment of deformations of vertebras.